Doing language im Deutschunterricht. Eine Analyse sprachbezogener Adressierungen in diskursiver Praxis - Büttner, Denise
Die Studie leistet einen empirisch-rekonstruktiven Beitrag zu einer machtkritisch ausgerichteten Fachdidaktik. Sie fokussiert den Deutschunterricht und die darin stattfindenden Interaktionen als diskursive Praxis, in der ein spezifisches Wissen in, über und angesichts von Sprache relevant gemacht wird. Für Subjektivierung ist jenes Wissen hochgradig wirkmächtig und bleibt den Akteur*innen im Prozess der schulischen Enkulturation doch größtenteils unbewusst. Darin liegt ein hohes Potential für die institutionelle (Re-)Produktion von Linguizismus.Vor diesem Hintergrund eröffnet die Studie einen Blick auf sprachbezogene Adressierungen, die in charakteristischer Weise vom Fach selbst ausgehen. Sie werden in (fach)didaktischen und pädagogischen Programmatiken breit kommuniziert und zeichnen sich bis auf die Ebene unterrichtlicher Praktiken ab. Um das Zusammenspiel von fachspezifischer Adressierung und Praktiken des ‚doing language‘ möglichst eng aufeinander beziehen und in rekonstruktionslogisch plausibilisierte Zusammenhänge bringen zu können, liegt der Arbeit ein wissenssoziologisch-diskursanalytischer Ansatz zugrunde.
Keywords: Diskursanalyse; Machtkritik; Sprache und Bildung; Rekonstruktive Unterrichtsforschung; Subjektivierung; Fachdidaktik

Measurement of Ultrashort Biphoton Correlation Times with an Integrated Two-Color Broadband SU(1,1)-Interferometer - Roeder, Franz; Pollmann, René; Stefszky, Michael; Santandrea, Matteo; Luo, Kai Hong; Quiring, V.; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
The biphoton correlation time, a measure for the conditional uncertainty in the temporal arrival of two photons from a photon pair source, is a key performance identifier for many quantum spectroscopy applications, with shorter correlation times typically yielding better performance. Furthermore, it provides fundamental insight into the effects of dispersion on the biphoton state. Here, we show that a characteristic dependence of the width of the temporal interferogram can be exploited to obtain insights into the amount of second-order dispersion inside the interferometer and to retrieve actual and Fourier-limited ultrashort biphoton correlation times of around 100 fs. In the presented scheme, we simultaneously measure spectral and temporal interferograms at the output of an SU(1,1) interferometer based on an integrated broadband parametric down conversion source in a Ti:LiNbO3 waveguide.

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland

Tailored metrics for assessing the quality of MBSE models - Gräßler, Iris; Wiechel, Dominik; Özcan, Deniz; Taplick, Patrick (Proceedings of the Design Society)
Abstract System models are used to merge relevant engineering artefacts and relationships. Therefore, a high model quality must be ensured. Currently, there is no method for defining company-specific metrics to assess system model quality. In a six-step research approach, a method is defined: (1) literature analysis on quality assessment approaches, (2) derivation of success factors, (3) evaluation of approaches, (4) development of a method, (5) application in automotive industry, and (6) evaluation. The method supports system engineers to derive tailored metrics to objectively assess the model quality.

Young Adult Diaspora Short Stories in the EFL Classroom: Approaching the Country of Reference Nigeria Through the Eyes of Adolescent Narrators - Bauer, Maike (Focus on Reading Young Adult (YA) Literature in the EFL Classroom and Beyond)

Tax Compliance Management Systeme in deutschen Betriebsprüfungen – Eine Analyse praktischer Erfahrungen - Schulz, Kim Alina; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Uncovering Impact of Innovation: Continuous Stakeholder Engagement through Scenario-based Systems Engineering - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Proceedings of the 21st ISCRAM Conference (ISCRAM 2024))
The importance of extreme weather situations is increasing due to their number and, above all, their impact on stakeholders in emergency response. They are characterized by cascading effects with global and local interdependencies. Extreme data must be included as a basis for decision-making. The impact in emergency response depends on diverse, multidisciplinary competencies required to interpret information. Scenarios are used in various forms of preparation: in exercises, but also for the design of information systems and validation. Based on literature, this article brings together different types of scenarios and related work in the field of Model-Based Systems Engineering. Using an exemplary case relating to possible pluvial urban floods, the added value resulting from a focus on the impact of innovative solutions is discussed. It is shown that the use of scenarios helps to make the desired impact assessable for decision-makers in all phases of research and development projects.

Investigation of Fluid Flow and Heat Transfer Characteristics of an Internally Channeled Tube Heat Exchanger under Laminar Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y. (energies)

The Imperative of Revival Strategies through Digital Transformation in the Cultural Sector - A Taxonomy Approach - Althaus, Maike; Hansmeier, Philipp (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))
Excellent Information Systems (IS) bachelor or master student theses have the potential to inform the scientific community about interesting findings about IS phenomena. However, transforming such theses into scientific working papers is not only time-consuming for the student and the supervisor, but also purely voluntary. Part of the problem is that few IS faculties offer any structured course for the transformation process as part of their curriculum. This significantly reduces the proportion of outstanding theses that are developed into working papers and, ultimately, into publications, resulting in a loss of knowledge for the broader IS community. To address this structural deficit, we aim to develop and implement a credit course and open educational resources (e.g., course schedule, slides, videos) that support students in developing their theses into publishable scientific research papers. This approach not only enriches the scientific discourse but also presents a research-oriented educational disruption for the IS community.
Keywords: Student Thesis; Scientific Publishing; Course Implementation

Erklären ist nicht gleich erklären. Wie erklärt man "gut" im Erklärvideo? - Risse, Sylvia (Praxis Deutsch)

A School Student Essay Corpus for Analyzing Interactions of Argumentative Structure and Quality - Stahl, Maja; Michel, Nadine; Kilsbach, Sebastian; Schmidtke, Julian; Rezat, Sara; Wachsmuth, Henning
Learning argumentative writing is challenging. Besides writing fundamentals such as syntax and grammar, learners must select and arrange argument components meaningfully to create high-quality essays. To support argumentative writing computationally, one step is to mine the argumentative structure. When combined with automatic essay scoring, interactions of the argumentative structure and quality scores can be exploited for comprehensive writing support. Although studies have shown the usefulness of using information about the argumentative structure for essay scoring, no argument mining corpus with ground-truth essay quality annotations has been published yet. Moreover, none of the existing corpora contain essays written by school students specifically. To fill this research gap, we present a German corpus of 1,320 essays from school students of two age groups. Each essay has been manually annotated for argumentative structure and quality on multiple levels of granularity. We propose baseline approaches to argument mining and essay scoring, and we analyze interactions between both tasks, thereby laying the ground for quality-oriented argumentative writing support.
Keywords: Annotation; Corpus; Argumentative Structure

DeepApprox: Rapid Deep Learning based Design Space Exploration of Approximate Circuits via Check-pointing - Awais, Muhammad; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (To apear in IEEE ISVLSI 2024)

Soziale Grenzen und Grenzbearbeitungen. Ein Zugang zur sozialwissenschaftlichen Bildungsforschung - Haker, Christoph; Otterspeer, Lukas (Bildungsforschung: Erziehungswissenschaftliche Perspektiven)
Der Beitrag führt in die von uns verfolgte Forschungsperspektive der sozialen Grenzen und Grenzbearbeitungen ein und bringt diese mit den Begriffen Bildung und Bildungsforschung zusammen. Unsere Theoretisierung beginnt mit einem sozialtheoretisch unterbestimmten Verständnis sozialer Grenzen und Grenzbearbeitungen. Dieses erhebt einerseits den Anspruch, nah an Alltagserfahrungen mit sozialen Grenzen und Grenzbearbeitungen zu sein. Andererseits ermöglicht es den Einstieg in ganz unterschiedliche Sozialtheorien und damit eine multiperspektivische Forschungspraxis. Dieses Potential plausibilisieren wir am Beispiel von Analysen zu Fragestellungen der Wissenschafts- und Rechtsextremismusforschung, die wir selbst durchgeführt haben. Für Bildung und Bildungsforschung sind in diesem Zusammenhang der Blick auf Bildungsprozesse, Bildungsinstitutionen und die Konzeption von Forschung als eine selbstreflexive Bildungspraxis relevant.

Mit tiergestützter Pädagogik soziale Teilhabe fördern! - Mombeck, Mona Maria

Tiergestützte Pädagogik. Ein Einblick: Grundlagen zum Einsatz von Schulhunden im (inklusiven) Unterricht - Mombeck, Mona Maria
Vortrag LMU München [online]

Asymptotics of extensions of simple $\mathbb Q$-algebras - Gundlach, Fabian; Seguin, Béranger (arXiv:2405.17286)
We answer various questions concerning the distribution of extensions of a given central simple algebra $K$ over a number field. Specifically, we give asymptotics for the count of inner Galois extensions $L|K$ of fixed degree and center with bounded discriminant. We also relate the distribution of outer extensions of $K$ to the distribution of field extensions of its center $Z(K)$. This paper generalizes the study of asymptotics of field extensions to the noncommutative case in an analogous manner to the program initiated by Deschamps and Legrand to extend inverse Galois theory to skew fields.

Nur Provokation oder doch politisches Statement? Der Spot "The Journey" von 84 Lumber aus dem Jahr 2017 - Janus, Richard; Müller, Emma (Weihnachts-Werbespots als moderne Krippenspiele)

Werbung, Krippenspiele und Religion. Einleitende Bemerkungen - Janus, Richard (Weihnachts-Werbespots als moderne Krippenspiele)